COMPARISON OF PHARMACOLOGY AGENTS EFFECT IN TREATING URETERAL STENT RELATED SYMPTOMS: SYSTEMATIC REVIEW & META-ANALYSIS OF RANDOMIZED CONTROLLED TRIAL¬ - Mubarak, Andi As'ad; Mahfuz, Muhammad Ainul; Aziz, Abdul; Dahlan, Muhammad Sopiyudin (Indonesian Journal of Urology, 2024)
Objective: We wish to update existing meta-analyses to assess the effectiveness of pharmacological agents against ureteral stent-related symptoms with better design of RCTs, as well as more valid and reliable measurement methods. Material & Methods: Relevant published articles up to February 2022 were obtained from PubMed, CENTRAL, Google Scholar, Science Direct, and DOAJ. All single-blind or double-blind RCTs with various comparisons using pharmacological agents and/or placebo in patients with ureteral stent-related symptoms, with outcome assessment using USSQ at week 1 and week 4 during stent placement was included in the study. Statistical parameter Mean Difference (MD) with 95% CI was used to measure effect size. The p value less than 0.05 indicates statistical significance. Results: Alpha blockers (2 studies, 85 samples) significantly reduced fourth week UIS compared to placebo (MD: – 5.46, 95% CI: – 7.47 to -3.46, I2 = 0%, P = < 0.001), and alpha blockers (2 studies, 42 samples) significantly reduced first week SIS compared to combination therapy (MD: – 0.82, 95% CI: – 1.56 to – 0.08, I2 = 0%, P = 0.03). The results of the meta-analysis of USSQ scores in other domains have no significant differences. Conclusion: Alpha blockers were better than placebo in reducing UIS due to ureteral stent in the fourth week of stent placement, and better than combination therapy in reducing SIS due to ureteral stent in the first-week post stenting. However, more RCTs are needed with larger samples and better designs to reach valid conclusions. Keywords: Stents, Randomized Controlled Trials as Topic, Single-Blind Method.